2018
DOI: 10.12659/msm.912961
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Fixation for Tibial Eminence Fractures: Comparison of Double-Row and Transosseous Anchor Knot Fixation Techniques with Suture Anchors

Abstract: BackgroundTibial eminence fractures often occur during sports participation, but the optimum choice of technique for treatment is still controversial. The aim of the current work was to compare the clinical outcomes of 2 new arthroscopic anchor fixation techniques for tibial eminence fracture.Material/MethodsWe included 72 isolated tibial eminence fracture patients treated at our hospital from October 2010 to August 2015; 37 patients received the classic double-row (DR) suture anchor fixation technique and 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The authors concluded that this technique is suitable for all types of TEFs, and is able to apply uniform planar compression to the avulsed fracture fragments rather than the point compression fixation from a single row of anchor, thereby promoting fracture healing and preventing fragmentation. Although Mann et al did not state whether their case was adolescents or not, this technique was quickly recognized and widely accepted, with several variations of the procedure ultimately being derived (30)(31)(32)(33)(34). Overall, due to the increasing popularity of arthroscopic manipulation techniques, the fact that anchor technique results in little damage to the epiphysis and fixation is very stable, it has gained popularity in recent years, showing the potential to become a mainstream surgery in the future.…”
Section: Anchorsmentioning
confidence: 99%
“…The authors concluded that this technique is suitable for all types of TEFs, and is able to apply uniform planar compression to the avulsed fracture fragments rather than the point compression fixation from a single row of anchor, thereby promoting fracture healing and preventing fragmentation. Although Mann et al did not state whether their case was adolescents or not, this technique was quickly recognized and widely accepted, with several variations of the procedure ultimately being derived (30)(31)(32)(33)(34). Overall, due to the increasing popularity of arthroscopic manipulation techniques, the fact that anchor technique results in little damage to the epiphysis and fixation is very stable, it has gained popularity in recent years, showing the potential to become a mainstream surgery in the future.…”
Section: Anchorsmentioning
confidence: 99%
“…Each technique has its pros and cons. [1][2][3][4][5][6][7][8] The goals of fracture fixation are early restoration of knee range of motion, minimization of ACL laxity, adequate stability to allow Abstract: Tibial spine/eminence fractures are uncommon fractures, usually seen in patients with open physes, and are considered as an equivalent to an ACL tear in adults. The aim of treatment is reduction of the fracture, restoring the ACL length for appropriate healing and avoiding complications.…”
Section: Introductionmentioning
confidence: 99%